Alianza Mundial para la Investigación de la peste porcina africana - Frías Lepoureau, María T.; Percedo Abreu, María I.; Perera González, Carmen L.; Zulueta, Juliane; Peláez Reyes, Manuel; Alfonso Zamora, Pastor (Revista de Salud Animal, 2022)
-